A Middle Cranial Fossa Dermoid Cyst Treated by an Endonasal Endoscopic Approach. Issue 4 (June 2015) - Durmaz, Abdullah; Yildizoğlu, Üzeyir; Polat, Bahtiyar; Binar, Murat
<x xml:space="preserve">Abstract</x> Abstract Dermoid cysts are rare, benign, congenital ectodermal inclusion cysts in the skull base, comprising skin supplements surrounded by squamous epithelium. In the period of embryological development, the cysts originate from ectodermal cells left behind in the cranial region by the closure of the neural tube and are primarily located at the midline, especially in the subarachnoid spaces. These lesions are usually asymptomatic and diagnosed incidentally. When the cysts reach large sizes, they can be symptomatic due to infection, rupture, or mass effect around neurovascular tissue. The cysts typically demonstrate accurate radiological diagnostic features. In this case report, we present a rare dermoid cyst in the middle cranial fossa, treated by an endonasal endoscopic approach. The endonasal endoscopic management of appropriate middle cranial fossa is discussed as a recent advance in the extended applications of endoscopic sinus surgery.